2014
DOI: 10.1080/15481603.2014.882564
|View full text |Cite
|
Sign up to set email alerts
|

The responses of vegetation water content (EWT) and assessment of drought monitoring along a coastal region using remote sensing

Abstract: This article retrieved the vegetation water content equivalent water thickness (EWT) information and the relevant parameters for the land surface from full-band TM remote sensing data. The effects of surface water heat flux and surface covering on the EWT were analyzed via studies of the regional land cover status and the combined EWT with land surface parameters. This article also analyzed the roles and limitations of EWT in drought monitoring combined with classification of the regional drought and regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Peñuelas et al [8, 9] used plant water content and the leaf relative water content to test the model developed from spectral reflectance data. At a canopy level and in larger scales, the quantification is more often expressed as equivalent water thickness (EWT) and canopy water content (CWC) [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Peñuelas et al [8, 9] used plant water content and the leaf relative water content to test the model developed from spectral reflectance data. At a canopy level and in larger scales, the quantification is more often expressed as equivalent water thickness (EWT) and canopy water content (CWC) [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al (2016) evaluated sixteen remote sensing drought factors and found that vegetation-related factors, such as NDVI, are more effective in capturing agricultural drought status in both arid and humid regions. Gao et al (2014) evaluated the equivalent water thickness (EWT), a measure of vegetation water content derived from the near-infrared (NIR) and the short-wave infrared bands, for regional drought monitoring. They found that EWT is strongly affected by vegetation density and cover type, and is therefore of limited use for monitoring moderate to severe drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is a very useful input to a number of primary productivity models based on simple light use efficiency considerations (Dinku, Funk, and Grimes al. 2008) passive microwave (PMW) sensors give better estimations than thermal infrared (TIR) sensors (Gruber and Levizzani 2008) Calculated from TIR or PMW sensors: high level of uncertainty in estimates (Hellmuth et al 2009;Dinku, Funk, and Grimes 2008;Gommes and Kayitakire 2013) Vegetation indices sensitive to drought (Black and Stephen 2014;Gao et al 2014) Production loss measured objectively (Chantarat et al 2013;Makaudze and Miranda 2010;Potter 2014) Good correlation with energy uptake by growing and senescent plants (Ceccato et al 2008;Duan et al 2012;Gao et al 2013;Phillips et al 2013) Not easily verifiable Validation is complex (Burke, de Janvry, and Quintero 2010) Availability of data For TIR sensor: spatially continuous acquisition of data over most of the globe (Dinku, Funk, and Grimes 2008) Availability of long archive (Gruber and Levizzani 2008) PMW sensors not geosynchronous: acquisition with low repetition rate (Hellmuth et al 2009;Dinku, Funk, and Grimes 2008) Short period of record ...…”
Section: Development Of An Index-based Insurance Product: Validation mentioning
confidence: 99%